2020
DOI: 10.1186/s13071-020-3915-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of predation and parasitism on the Anopheles gambiae mosquito

Abstract: Background: A good understanding of mosquito ecology is imperative for integrated vector control of malaria. In breeding sites, Anopheles larvae are concurrently exposed to predators and parasites. However, to our knowledge, there is no study on combined effects of predators and parasites on development and survival of larvae and their carry-over effects on adult survivorship and susceptibility to further parasite infection. Methods:This study focused on effects of the nymphs of the dragonfly Pantala flavescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 54 publications
(99 reference statements)
5
18
0
Order By: Relevance
“…Compared to temporary habitats, permanent breeding habitats tend to support higher densities of predator and competitor taxa [ 21 ]. Predation on larvae by aquatic insect predators affects larval development, impacts the adult sex ratio at emergence and subsequently influences the adult life-history traits such as body size, fecundity and longevity [ 22 , 23 ]. The presence of predators and competitors in aquatic larval habitats lowers their chances of being chosen as oviposition sites by female An.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to temporary habitats, permanent breeding habitats tend to support higher densities of predator and competitor taxa [ 21 ]. Predation on larvae by aquatic insect predators affects larval development, impacts the adult sex ratio at emergence and subsequently influences the adult life-history traits such as body size, fecundity and longevity [ 22 , 23 ]. The presence of predators and competitors in aquatic larval habitats lowers their chances of being chosen as oviposition sites by female An.…”
Section: Introductionmentioning
confidence: 99%
“…was not related to habitat disturbance or predation. However, Ong'wen et al (2020) found that the presence of a predator (dragonfly nymphs) decreases development time of An. gambiae larvae, as well as increasing the susceptibility of emerging adults to a parasite (fungus).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies on predator–prey interactions in mosquitoes have shown both reductions in prey density as well as changes in important aspects of prey, such as development time, size, fecundity, and pathogen infection, that may alter the risk of disease transmission (Roux et al 2015, Huang et al 2017, Roux and Robert 2019, Ong’wen et al 2020, Alomar et al 2020). For instance, the introduction of predatory mosquito Toxorhynchites moctezuma larvae resulted in reduction of larval population density of Aedes aegypti (Tikasingh and Eustace 1992).…”
Section: Introductionmentioning
confidence: 99%